Middle East water conflicts and directions for conflict resolution - Wolf, Aaron T. (International Food Policy Research Institute, 1996)
In looking toward 2020, one of the most severe problems to be faced is an impending shortage of adequate supplies of fresh water essential for drinking and for growing crops. The Middle East, where a few waterways serve large areas of land belonging to a number of nations, is the place where strife over water is most likely to erupt. This paper examines the past--how water in the Middle East came to be divided as it is today--and looks at possible solutions for alleviating a water crisis and the resulting political tensions.